Effects of pre-rigor injection of sodium citrate or acetate, or post-rigor injection of phosphate plus salt, on post-mortem glycolysis, ph decline, and pork quality attributes - Stephens, J.W.; Dikeman, Michael E.; Unruh, John A.; Haub, M.D.; Tokach, Michael D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Forty pork carcass sides were assigned to one of four treatments: pre-rigor citrate (CIT) or acetate (ACE) injection, post-rigor phosphate plus salt (PHOS) injection, and noninjected control (CON). Loins in 20 sides were injected 50 min post-mortem with 4% solutions of CIT or ACE to approximately 110% of projected loin weights, and 10 PHOS-treated loins were injected at 24 h postmortem to 106.6% with a 4.4% PHOS plus 2.2% salt solution. Although CIT increased pH (P<0.05), neither CIT nor ACE altered (P>0.05) glycolytic metabolite concentrations. The pH increase in CIT-injected muscle was most likely due to its buffering ability rather than glycolytic inhibition. Citrate improved tenderness without the detrimental effects on color or flavor found with PHOS plus salt, but neither CIT nor ACE altered glycolytic metabolites or improved firmness, wetness, or fresh visual color over CON. Poor flavor attributes of the ACE treatment will discourage its use as an ingredient for pork enhancement solutions.
Swine research, 2005 is known as Swine day, 2005
Keywords: Pork; Pre-rigor injection; Citrate; Acetate; Phosphate; Swine